Long-term maintenance of luteinizing hormone-responsive testosterone formation by primary rat Leydig cells in vitro. (15th November 2018) - Wang, Yiyan; Huang, Shengsong; Wang, Zhao; Chen, Fenfen; Chen, Panpan; Zhao, Xingxing; Lin, Han; Ge, Renshan; Zirkin, Barry; Chen, Haolin
Abstract: The inability of cultured primary Leydig cells to maintain luteinizing hormone (LH)-responsive testosterone formation in vitro for more than 3–5 days has presented a major challenge in testing trophic effects of regulatory factors or environmental toxicants. Our primary objective was to establish culture conditions sufficient to maintain LH-responsive testosterone formation by Leydig cells for at least a month. When isolated rat adult Leydig cells were cultured in DMEM/F12 and M199 culture medium containing insulin (10μg/ml), PDGFAA (10 ng/ml), lipoprotein (0.25 mg/ml), horse serum (1%) and a submaximal concentration of LH (0.2 ng/ml), the cells retained the ability to produce testosterone in vitro for at least 4 weeks. By using the longer-term culture conditions of this system, we were able to detect suppressive effects on testosterone production by low levels of the toxicant MEHP (mono-(2-ethylhexyl) phthalate), an active metabolite of the plasticizer DEHP, that were not detected by short-term culture. Highlights: A novel culture medium for the long-term maintenance of primary Leydig cells in vitro. Insulin and PDGFAA play important roles in maintaining steroidogenesis in vitro. LHCGR and CYP17A1 are particularly sensitive to long-term culture. The long-term culture system is useful to test chronic effects of environmental toxins.